35 Pain in advanced disease: initial findings from a qualitative interview study with british south asians in leeds and bradford, UK. (13th October 2019) - Clarke, Gemma; Ahmed, Shenaz; Nazar, Wali; Rayment, Clare; Bennett, Michael
Abstract : Background: Population projections indicate that by 2051, the Black, Asian and Minority Ethnic (BAME) populations of England and Wales will rise to 3.8 million people aged 65 years and over, and 2.8 million aged 70 and over (Lievesley, 2010). This has important implications for palliative care services. Current evidence on ethnicity and palliative care is limited, and is often solely focused on access to services (Calanzani et al., 2013). Evidence is particularly limited for British South Asian populations (Shabnam, et al, 2019). South Asians have a high burden of life-limiting and chronic diseases compared to other groups (Nair and Prabhakaran, 2012). This study focuses on pain management, the impact of culture, and the quality of services for British South Asians with advanced disease. Aim: To explore the attitudes and perceptions of British South Asians with advanced disease concerning pain, pain management, and expression of pain; and to examine the differences in service provision. Methods: Qualitative interviews (N=25) with individuals who have serious life-limiting disease, are experiencing pain as a symptom, or having their pain controlled, and are from a South Asian background currently living in Leeds or Bradford UK. Fieldwork was undertaken in 2019. Interviews were audio recorded, transcribed verbatim and analysed using NVivo and Thematic Analysis (Braun and Clarke, 2006). Discussion: Key themes: experiences of pain and pain management related to cultural background; help-seeking behaviour and barriers; strong pain management at the end of life; and differences between those utilising specialist palliative care services and those receiving care elsewhere.